Heart size, heart function, and plasma B-type natriuretic peptide levels after transcatheter closure of patent ductus arteriosus - Mulyadi M. Djer; Sudigdo Sastroasmoro; Bambang Madiyono (Indonesian Pediatric Society Publishing House, 2013)
Background Patent ductus arteriosus (PDA) is a common congenital heart disease causing some blood in the aorta to flow into the pulmonary artery (PA), resulting in dilatation of the left atrium (IA) and left ventricle (LY), increased B-type natriuretic peptide (BNP) level, and the development of h eart failure. Objectives To evaluate the clinical course, changes in heart size and function, and BNP level after transcatheter closure of PDA using the Amplatzer® duct occluder (ADO). Methods This quasi-experimental study used a one-group, pretestposttest design, and was done on PDA patients who underwent transcatheter closure using ADO. The outcomes measurements were performed four times, namely, before the procedure and at one, three, and six months after the procedure. Results were compared using a serial time analysis. Outcomes measured were heart failure scores, chest x-ray (CXR) and echocardiography findings, and plasma BNP level. Results There were 23 PDA patients enrolled, of which 12 were females. Subjects' median bodyweight was 11 (range 6.6 to 55) kg. Prior to PDA closure, 12 subjects had mild heart fa ilure (class II) and 7 had moderate heart failure (class III). On follow-up at one month after the procedure, all subjects had improved heart failure scores (P<0.0001), and no heart failure was found on further follow up. Likewise, there was a decreased mean cardiothoracic ratio (CTR) from 58 to 55% at 1-month (P = 0.001), and also from 55 to 52% at3-month follow up (P<0.0001), but no further decrease was found afterwards (P = 0.798). The left atrium/aorta (LA/Ao) ratio measured by echocardiography also showed a statistically significant decrease from 1.6 prior to the procedure to 1.3 (P<0.0001) in the first month, but it remained stable afterwards. Diastolic function, represented by peak E and A waves also significantly decreased from 127 and 91 cm/sec, before the procedure, to 90 and 68 cm/sec, respectively, at 1 month follow-up (P <0.0001 and P < 0.0001, respectively) . However, there were no statistically significant changes in E/ A ratio, ejection fract ion and fractional shortening. Plasma BNP level significantly decreased from 58 pg/mL before the procedure to 28 pg/mL at 1 month follow-up (P= 0 .001), but no further significant decrease was observed afterwards. Conclusion After PDA closure with ADO, we observe significant improvements in heart failure scores, heart size, diastolic function, and BNP level of our subjects especially in the first month after the procedure.